POLA MAKAN DAN STATUS GIZI KELUARGA ETNIS TIONGHOA KELURAHAN ASAM KUMBANG KECAMATN MEDAN SELAYANG TAHUN 2014 - Susianita Pangaribuan; Evawany Y Aritonang; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT                Food consumption pattern  of  Tionghoa ethnic is  affected by  cultur factor  that has existed among generations. The family in choose the daily food menu. This study is a descriptive survey in order to the food consumption pattern and nutritional status of the ethnic Tionghoa family at kelurahan Asam Kumbang Kecamatan Medan Selayang. The population in this study are all ethnic Tionghoa  family at Kelurahan Asam Kumbang Kecamatan Medan Selayang that is 104 families. The sample is a portion of the population that is 51 Families. Data collection forms using diet Food List and Food Frequency. Nutritional status data obtained by weighing and measuring the height            The results showed that every day ( always ) ethnic Tionghoa families eat rice, meat and vegetables but fruits not every day. Good energy consumption of ethnic Tionghoa families can see from 78.4 % consume adequate energy ( ≥AKEK ) and for protein consumption 96.1 % consume adequate protein (≥AKPK). Father to be a priority in the distribution of food. ethnic Tionghoa families food with high value is pork. Ethnic Tionghoa families Food tabo is beef. Nutritional status of the family are in the normal category               Based on this research, it is expected distribution of food in the family based on nutritional needs, important to have menu cycle so that the food well-organized terms kind of food, frequency of food and the amount of food nor variation of food.   Keywords: food consumption patterns, Tionghoa ethnic, nutritional status of family